Acesso e permanência de educandos com deficiências em uma escola municipal de Parintins, no baixo Amazonas: impactos nos processos de ensino e aprendizagem - Matos, Carlem Rafaela Soares de (Brasil, 2023)
Abstract: This research sought to highlight the importance of accessibility in public and private spaces that provide individuals with disabilities and reduced mobility with a better quality of life. As for the procedures, the method used was field research with a sample of 02 subjects. The following evidence sources were chosen: semi-structured interview, documents, informal direct observation and physical artifacts. It is worth highlighting what can be considered the major challenges for schools in terms of access for students with disabilities: Breaking down existing barriers, especially attitudinal ones; Predict and provide accessibility conditions (physical, communicational and pedagogical) and; create alternatives to avoid exclusionary practices by teachers. In this sense, an education that values the presence of all students lacks investments in actions, adequate materials, teaching qualifications, architectural suitability, but, above all, investments in actions that combat inappropriate and prejudiced attitudes. Keywords: Accessibility; Deficiency; Mobility; Teachers; Education.